2013
DOI: 10.3168/jds.2012-6269
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endometrial cytology during estrous cycle and cutoff points for the diagnosis of subclinical endometritis in grazing dairy cows

Abstract: The objectives of this study were to assess the effect of the stage of estrous cycle on the percentage of endometrial polymorphonuclear cells (PMN) obtained by cytobrush to determine cutoff values for the diagnosis of subclinical endometritis under pastoral conditions, to measure the prevalence of subclinical endometritis 21 to 62d in milk (DIM), and to evaluate the effect of subclinical endometritis on reproductive performance in grazing dairy cows. The first experiment was conducted on a commercial dairy far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 23 publications
11
97
4
5
Order By: Relevance
“…On the other hand, the cut-off point of % PMN established for positive cytology may have influenced the agreement between the two techniques, since it was found that about 15% of healthy uteri diagnosed by histology were classified with positive cytology. As previously reported by Madoz et al (2013), in the present study, cytology outputs were not influenced by the phase of the estrus cycle at the time of diagnosis. However, by using biopsy, a higher degree of inflammatory infiltration could be detected during the follicular phase of the cycle.…”
Section: Agreement Between Diagnosis Methodssupporting
confidence: 74%
“…On the other hand, the cut-off point of % PMN established for positive cytology may have influenced the agreement between the two techniques, since it was found that about 15% of healthy uteri diagnosed by histology were classified with positive cytology. As previously reported by Madoz et al (2013), in the present study, cytology outputs were not influenced by the phase of the estrus cycle at the time of diagnosis. However, by using biopsy, a higher degree of inflammatory infiltration could be detected during the follicular phase of the cycle.…”
Section: Agreement Between Diagnosis Methodssupporting
confidence: 74%
“…According to numerous authors the endometritis is to be suspected in cows with the PMNs percentage exceeding 4-5% on 45-50 day after parturition (Barański et al, 2012;Kasimanickam et al, 2004;Madoz et al, 2014). Madoz et al (2013) stress that the percentage of PMNs does not change in the estrus period cycle in healthy cows. It is confirmed by the results obtained in the authors' investigations in which small differences between the neutrophils percentage in cows in heat and those outside the estrus period were not statistically significant (p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Endometrial cytological samples were collected from cows by using a modified sterile Cytobrush Plus GT (Medscand Medical, Germany) (Madoz et al, 2013). The handle was shortened to 2 cm and made thread-like to enable insertion into a stainless steel rod (artificial insemination AI gun 65 cm in length, 4 mm outside diameter).…”
Section: Endometrial Cytology Using Cytobrush Methodsmentioning
confidence: 99%